Pengaruh Kualitas Audit, Kepemilikan Manajerial, Kepemilikan Institusional Terhadap Manajemen Laba Perusahaan Perbankan - Jessica Aurelia Winoto; Rousilita Suhendah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of audit quality, managerial ownership, and institutional ownership on earnings management. The research sample was selected using the purposive sampling method. The observations were based on data from 42 banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, resulting in a total of 150 data samples. The data were processed using panel data regression analysis with the assistance of the Eviews12 program, and the most suitable estimation model was the Common Effect Model (CEM). To measure the dependent variable, namely earnings management, this study employed discretionary accruals using the Modified Jones Model. Based on the data analysis results, this study shows that audit quality, proxied by the size of the Public Accounting Firm (KAP), has a positive effect on earnings management. Conversely, institutional ownership has a negative effect on earnings management, while managerial ownership has no effect on earnings management.